The incidence of head and neck cancer in interventional cardiologists - Pretorius, Izak Stefanus; Ntutuka, Ntuthuko Lona; Hattingh, Paul; de Klerk, Cornelia; Mongane, Modisenyane (SA Heart Journal, 2024)
The occupational risk to interventional cardiologists related to using X-rays in the catheterisation laboratory (cath lab) includes a range of radiation-induced effects. The primary concern is the possibility of developing head and neck malignancies. A literature review of reports on developing head and neck malignancies among interventional cardiologists was conducted. Several individual cases of head and neck malignancies have been reported, predominantly on the left side. However, these studies do not have a sufficient sample size to generalise the results. Based on the available reports, it is concluded that head and neck malignancies are unlikely to constitute an occupational risk for interventional cardiologists. More research is required to establish whether head and neck malignancies are more prevalent among interventional cardiologists.